2001
DOI: 10.1207/s15374424jccp3004_13
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Patterns and Sleep Disruptions in Kindergarten Children

Abstract: Assessed sleep patterns and sleep disruptions in kindergarten children and investigated the relation between sleep measures derived from objective and subjective evaluation methods. The sleep patterns of 59 normal kindergarten children (mean age = 5.5 years) were monitored for 4 to 5 consecutive nights by means of activity monitors (actigraph) and by means of parental daily sleep logs. The correlation between the actigraphic measures and the daily parental logs indicated that parents were accurate reporters of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
117
4
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(129 citation statements)
references
References 57 publications
7
117
4
1
Order By: Relevance
“…13,14 We hypothesized, according to the previous literature, 7,8 that for sleep start, sleep end, and sleep duration actigraphy and diary data would agree well, while questionnaire data may differ substantially when compared with actigraphy but less so with diary data; we expected a lower agreement between methods in respect to nocturnal waking.…”
Section: Arch Pediatr Adolesc Med 2008;162(4):350-358mentioning
confidence: 94%
See 1 more Smart Citation
“…13,14 We hypothesized, according to the previous literature, 7,8 that for sleep start, sleep end, and sleep duration actigraphy and diary data would agree well, while questionnaire data may differ substantially when compared with actigraphy but less so with diary data; we expected a lower agreement between methods in respect to nocturnal waking.…”
Section: Arch Pediatr Adolesc Med 2008;162(4):350-358mentioning
confidence: 94%
“…The source of information (subjective vs objective) in the evaluation of sleep-wake patterns has been a topic in several studies with different populations (adults vs children, normal vs clinical samples) and different devices. [4][5][6][7][8] It has been repeatedly demonstrated that subjective, compared with objective, reports are limited by the restricted and biased knowledge that parents have about children's sleep. 7 However, parental reports remain a time-and costeffective way of collecting data in research and clinical settings.…”
Section: Arch Pediatr Adolesc Med 2008;162(4):350-358mentioning
confidence: 99%
“…After this phase, all parents and children underwent a separate interview developed by Muris et al [28] to assess nighttime fears in children. Parents received daily sleep logs [48] and an actigraph (AMA-32, Ambulatory Monitoring Inc., Ardsley, NY, USA) for a week of monitoring and also the Child Behavior Checklist (CBCL) [2,55] for completion during this week. At the end of the first session, children were randomly assigned to one of two intervention groups: HPI and HPI-r groups.…”
Section: Methodsmentioning
confidence: 99%
“…25,37,38 Furthermore, normative developmental data have been collected, and developmental changes in sleep patterns have been established. 38,[43][44][45][46] Actigraphic measures were averaged across the 5 to 7 days of monitoring. Actigraphic sleep measures included 1) sleep-onset time, 2) sleep period (from sleep-onset time to morning awakening time), 3) true sleep time (sleep time excluding all periods of wakefulness), 4) sleep percentage (percentage of true sleep time in the total sleep period), and 5) number of night wakings that lasted Ն5 minutes.…”
Section: Actigraphymentioning
confidence: 99%